School based teacher training : a handbook for tutors and mentors - Jarvis, Joy.; White, Elizabeth (Elizabeth J.) (Los Angeles : Sage, 2013)
A handbook for coaching and mentoring teachers and trainee teachers in schools.
Includes bibliographical references (p. 85-87) and index.
Professional.
Professional
Keywords: Teachers -- Training of; Teachers -- Training